Capital Structure, Ownership Structure and Corporate Governance of SMEs in Ghana - Ibrahim Anyass Ahmed (Journal of Accounting, Business and Management (JABM), 2019)
The purpose of this paper is to investigate the relationship between three variables; capital structure, ownership structure and corporate governance. Although these issues have been largely researched, less attention has been focused on small and medium enterprises (SMEs). At the time of this study, evidence was not found for a study analyzing all three variables in relation to SMEs, within the context of a developing country. This current study examines the link between capital structure, ownership structure, and corporate governance. Using an appropriate regression model, the study assesses how governance mechanisms and ownership decisions affect the choice of financing SMEs. The results show a positive relationship for all corporate governance variables except for board size. Ownership structure is found to be positive and significantly related to capital structure. The signs indicated by control variables are those which are in consonance with conventional capital structure literature. Generally, ownership and corporate governance are found to affect the financing mix of SMEs in Ghana.